2022
DOI: 10.3390/ijms231911589
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Free Light Chains (FLCs) Synthesis in Response to Exposure to SARS-CoV-2

Abstract: The aim of this study is to assess the synthesis of kappa (κ) and lambda (λ) free light chains (FLCs) in the serum of patients with COVID-19. All the 120 serum samples were collected from patients with COVID-19 and from healthy controls (vaccinated and non-vaccinated against SARS-CoV-2). FLCs, IgG total, IgG4, IgG anti-Nucleocapsid (N), anti-spike S1 receptor binding domain (S-RBD) antibodies and IL-6 were measured according to the manufacturers’ instructions. The concentrations of anti-N IgG, IgG total, IgG4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The binding of IgLC to human neutrophils was shown to induce the chemokine IL-8 (CXCL8). This suggests that IgLC could play a role in the pulmonary inflammatory response observed in COPD patients (20).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The binding of IgLC to human neutrophils was shown to induce the chemokine IL-8 (CXCL8). This suggests that IgLC could play a role in the pulmonary inflammatory response observed in COPD patients (20).…”
Section: Discussionmentioning
confidence: 94%
“…The researchers found that levels of IgLC were elevated in animals with emphysema and right heart enlargement caused by chronic cigarette smoke inhalation. In patients with moderate to severe COPD, increased serum levels of IgLC were found compared with controls (20). The binding of IgLC to human neutrophils was shown to induce the chemokine IL-8 (CXCL8).…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that the most specific and the least likely to cross-react antibodies are those directed against the S1 protein receptor binding domain, so we tested these antibodies in our research [ 26 ]. At visit 1, the presence of these antibodies was found in almost 82% of the study group.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a kFLC index cut-off equal to 4.7, compared to the OCB and IgG index, showed greater sensitivity (92.9%) but lower specificity (77.5%) [28]. In addition, considering the advantages regarding the use of the K-index (rapid and automated technique) compared to OCBs, some authors have proposed the use of the K-index as a primary marker instead of the evaluation of OCBs to highlight the intrathecal synthesis of IgG [3,28,38,61].…”
Section: Diagnostic Performance Of Ocbs and K-index In Msmentioning
confidence: 99%